(untitled) (Analysis in Theory and Applications, 2018)
In the present paper, we establish direct and converse theorems for weighted Bernstein-Durrmeyer operators under weighted L^p−norm with Jacobi weight w(x) = x^α(1−x)^β. All the results involved have no restriction α, β